2018
DOI: 10.1055/a-0653-7135
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Determinants of Impaired Pulmonary Function in Patients with Newly Diagnosed Type 2 Diabetes Mellitus

Abstract: Recent-onset type 2 diabetes patients exhibit reductions in features of pulmonary function, which might be at least in part resulting from glucotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…Decline In Lung Volumes, FEV1, FVC and Diffusion capacity ensue with aging as well as in obese subjects with further exaggeration in presence of diabetes leading to worsening restrictive pulmonary disease frequently resulting in onset of Cor pulmonale [120] [121] [122] [123] These manifestations may be attributed to unifying mechanism; lack of entry of Glucose into alveolar cells and respiratory Muscles of Chest, Diaphragm secondary to insulin resistance as well as a relative or absolute decline in insulin secretion [104].…”
Section: Pulmonary Dysfunctionmentioning
confidence: 99%
“…Decline In Lung Volumes, FEV1, FVC and Diffusion capacity ensue with aging as well as in obese subjects with further exaggeration in presence of diabetes leading to worsening restrictive pulmonary disease frequently resulting in onset of Cor pulmonale [120] [121] [122] [123] These manifestations may be attributed to unifying mechanism; lack of entry of Glucose into alveolar cells and respiratory Muscles of Chest, Diaphragm secondary to insulin resistance as well as a relative or absolute decline in insulin secretion [104].…”
Section: Pulmonary Dysfunctionmentioning
confidence: 99%
“…5,6 Studies conducted in patients with type 2 diabetes mellitus demonstrated that hs-CRP associates negatively with lung function. 6,7 Insulin resistance and hyperinsulinemia Insulin resistance, especially seen in type 2 diabetes, contributes to increased insulin levels which leads to increased airway smooth muscle (ASM) mass and contractility that decreases muscle strength in the long run. Increased respiratory smooth muscle mass also leads to airway hypersensitivity and activation of epithelial mesenchymal trophic unit leading to airway remodeling.…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…5,6 Studies conducted in patients with type 2 diabetes mellitus demonstrated that hs-CRP associates negatively with lung function. 6,7…”
Section: Chronic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studien zeigen zwar eine Assoziation zwischen Lungenfunktionseinschränkungen und Blutglukoseauch bei Patienten ohne Diabetes mellitus. Dennoch gibt es keine Daten, die belegen, dass durch eine Verbesserung der Stoffwechselsituation auch eine Verbesserung der Lungenfunktion erreicht wird [23,24,38]. In einer Subgruppenanalyse von Patienten mit IPF und Diabetes mellitus konnte gezeigt werden, dass eine Metformintherapie ebenfalls keine positiven Effekte auf die Lungenfibrose hat [39].…”
Section: Therapeutische Ansätzeunclassified